Outcomes including liver histology after liver transplantation for chronic hepatitis B using oral antiviral therapy alone. Issue 12 (December 2015) - Fung, James; Lo, Regina; Chan, See‐Ching; Chok, Kenneth; Wong, Tiffany; Sharr, William; Cheung, Tan‐To; Chan, Albert C. Y.; Dai, Wing‐Chiu; Sin, Sui‐Ling; Ng, Irene; Lai, Ching‐Lung; et al.
Abstract : The outcomes of hepatitis B virus (HBV)–related hepatitis after liver transplantation (LT) without hepatitis B immune globulin (HBIG) is not well documented. This study aims to determine the outcomes of chronic hepatitis B (CHB) patients using an HBIG‐free regimen. All biopsies performed 3 months or more after LT in consecutive CHB patients transplanted from 2003 to 2012 were reviewed. None of the patients received HBIG. Results of all liver histologies were reviewed to determine the cause of graft dysfunction. Of the 435 patients transplanted during this period, 263 liver biopsies were performed in 144 patients. Thirty‐six patients were positive for hepatitis B surface antigen (HBsAg) with undetectable HBV DNA at the time of biopsy, and none had histological evidence of HBV infection. Of the 263 biopsies, 44 (17%) had evidence of fibrosis. There was a significantly higher rate of fibrosis in those with large duct obstruction compared to those without (51% versus 9%, respectively; P  < 0.001). Of the 291 patients without a liver biopsy during the same period, 43 were HBsAg+. Seven patients had evidence of virological rebound, of whom 6 had evidence of rtM204V/I mutation and 1 had recurrence of hepatocellular carcinoma with low‐level rebound and wild‐type virus. In conclusion, for patients without virological rebound, positive serum HBsAg was not associated with histological evidence of HBV‐related hepatitis after LT. To prevent virological rebound, nucleos(t)ide analogues with higher barriers to resistance should be used. Liver Transpl 21:1504‐1510, 2015 . © 2015 AASLD.